The role of levosimendan in phosphine-induced cardiotoxicity: evaluation of electrocardiographic, echocardiographic, and biochemical parameters. (22nd November 2021) - Armandeh, Maryam; Bameri, Behnaz; Baeeri, Maryam; Haghi-Aminjan, Hamed; Rahimifard, Mahban; Hassani, Shokoufeh; Hooshangi Shayesteh, Mohammad Reza; Khalid, Madiha; Samadi, Mahedeh; Hosseini, Rohollah; Masoudi Fard, Majid; Abdollahi, Mohammad
Abstract: Aluminum phosphide (AlP) causes serious poisoning in which severe cardiac suppression is the significant lethal consequence. According to evidence, levosimendan can exert outstanding cardiac support and protection in different pathological conditions. This study aimed to investigate the mechanisms by which levosimendan may alleviate cardiovascular toxicity due to AlP intoxication in the rat model. The groups included control group (normal saline only), sole levosimendan groups (12, 24, 48 μg/kg), AlP group (10 mg/kg), and AlP + levosimendan groups receiving 12, 24, 48 μg/kg levosimendan intraperitoneally 30 min after AlP administration. Electrocardiographic (ECG) parameters (QRS and PR duration and ST height), heart rate, and blood pressure were monitored for 180 minutes. Also, after 24 h of poisoning, echocardiography was applied to assess left ventricle function. Evaluation of the biochemical parameters in heart tissue, including mitochondrial complexes I, II, IV activity, ADP/ATP ratio, the rate of apoptosis, malondialdehyde (MDA), lactate, and troponin I levels, were done after 12 and 24 h. AlP-induced ECG abnormalities (PR duration and ST height), reduction in heart rate, blood pressure, cardiac output, ejection fraction, and stroke volume were improved by levosimendan administration. Besides, levosimendan significantly improved complex IV activity, the ADP/ATP ratio, apoptosis, MDA, lactate, and troponin I level following AlP-poisoning. Our results suggest that levosimendan might alleviate AlP-induced cardiotoxicity by modulating mitochondrial activity and improving cardiac function. However, the potential clinical use of levosimendan in this toxicity needs more investigations.